2023
DOI: 10.3389/fnins.2023.1166973
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering mechanisms of action of ACE inhibitors in neurodegeneration using Drosophila models of Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is a devastating neurodegenerative disorder for which there is no cure. Recently, several studies have reported a significant reduction in the incidence and progression of dementia among some patients receiving antihypertensive medications such as angiotensin-converting enzyme inhibitors (ACE-Is) and angiotensin receptor blockers (ARBs). Why these drugs are beneficial in some AD patients and not others is unclear although it has been shown to be independent of their role in regulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 120 publications
0
1
0
Order By: Relevance
“…There is some evidence to suggest that RAS inhibitors, such as ACEIs and ARBs, may have beneficial effects in AD. The mechanisms by which these drugs affect AD are not yet fully understood, but studies using Drosophila models of AD have shown that ACEIs and ARBs can suppress neuronal cell death and memory defects, suggesting that they may target the amyloid pathway [ 134 , 135 ].…”
Section: Neuroprotective Effects Of Renin Inhibitorsmentioning
confidence: 99%
“…There is some evidence to suggest that RAS inhibitors, such as ACEIs and ARBs, may have beneficial effects in AD. The mechanisms by which these drugs affect AD are not yet fully understood, but studies using Drosophila models of AD have shown that ACEIs and ARBs can suppress neuronal cell death and memory defects, suggesting that they may target the amyloid pathway [ 134 , 135 ].…”
Section: Neuroprotective Effects Of Renin Inhibitorsmentioning
confidence: 99%